2015
DOI: 10.1242/dev.115139
|View full text |Cite
|
Sign up to set email alerts
|

JNK Signaling is necessary for a Wnt and stem cell dependent regeneration program

Abstract: Regeneration involves the integration of new and old tissues in the context of an adult life history. It is clear that the core conserved signalling pathways that orchestrate development also play central roles in regeneration, and further study of conserved signalling pathways is required. Here we have studied the role of the conserved JNK signalling cascade during planarian regeneration. Abrogation of JNK signalling by RNAi or pharmacological inhibition blocks posterior regeneration and animals fail to expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…In contrast, the role of stress-induced MAPK pathways in regeneration is only poorly investigated. A joint activation of both stress inducible MAPK pathways was so far only reported for axonal regeneration in C. elegans and imaginal disc regeneration in Drosophila (Nix et al, 2011;Santabarbara-Ruiz et al, 2015), while most studies either focus on ERK activation during regeneration (Makanae et al, 2013;Owlarn et al, 2017;Suzuki et al, 2007;Yun et al, 2014) or p38/JNK (Chen et al, 2007;Tejada-Romero et al, 2015), our data indicate that these pathways do not work independently of one another, but participate in an extensive cross-talk. Inhibitor experiments revealed that p38/JNK interacts with Erk1/2 as potential antagonist.…”
Section: The Injury Stimulusmentioning
confidence: 56%
See 1 more Smart Citation
“…In contrast, the role of stress-induced MAPK pathways in regeneration is only poorly investigated. A joint activation of both stress inducible MAPK pathways was so far only reported for axonal regeneration in C. elegans and imaginal disc regeneration in Drosophila (Nix et al, 2011;Santabarbara-Ruiz et al, 2015), while most studies either focus on ERK activation during regeneration (Makanae et al, 2013;Owlarn et al, 2017;Suzuki et al, 2007;Yun et al, 2014) or p38/JNK (Chen et al, 2007;Tejada-Romero et al, 2015), our data indicate that these pathways do not work independently of one another, but participate in an extensive cross-talk. Inhibitor experiments revealed that p38/JNK interacts with Erk1/2 as potential antagonist.…”
Section: The Injury Stimulusmentioning
confidence: 56%
“…Most vertebrates have only a limited capacity to regenerate but some animals like cnidarians and planarians can regenerate their whole body. A conserved aspect of regeneration is that signaling pathways and GRNs (gene regulatory networks) that are involved in embryonic development become re-activated during the regeneration process Petersen, 2015, 2018;Petersen and Reddien, 2011;Tejada-Romero et al, 2015;Tewari et al, 2018;Vriz et al, 2014;Wurtzel et al, 2015). It is poorly understood, however, how the initial injury triggers pattern formation to replace lost structures in highly regenerating animals and tissues, and why this does not occur in non-regenerative animals and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of Wnt signaling components β -catenin-1 , wnt1, Evi/wntless, Dvl-1/2 and teashirt causes regeneration of ectopic heads ( Gurley et al, 2008 ; Iglesias et al, 2008 ; Petersen and Reddien, 2008 ; Petersen and Reddien, 2009 ; Owen et al, 2015 ; Reuter et al, 2015 ); conversely, inhibition of APC or notum can cause regeneration of ectopic tails ( Gurley et al, 2008 ; Petersen and Reddien, 2011 ). Other pathways participate in head or tail regeneration, with Hedgehog signaling influencing injury-induced wnt1 expression ( Rink et al, 2009 ), several transcription factors required for head formation ( prep, foxD, zic-1/zicA, pbx, egr-4) ( Felix and Aboobaker, 2010 ; Blassberg et al, 2013 ; Chen et al, 2013 ; Fraguas et al, 2014 ; Scimone et al, 2014 ; Vásquez-Doorman and Petersen, 2014 ; Vogg et al, 2014 ) and/or tail formation ( junli-1, pitx, pbx ) ( Blassberg et al, 2013 ; Chen et al, 2013 ; Currie and Pearson, 2013 ; Marz et al, 2013 ; Tejada-Romero et al, 2015 ), and influenced by gap junction and calcium signaling ( Oviedo et al, 2010 ; Zhang et al, 2011 ). However, comparatively little is known about the restoration of positional information along the head-to-tail body axis through regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…MAPK signaling, through both ERK and JNK pathways, is important in neoblast control and blastema differentiation in planaria [56,57] and JNK signalling has been specifically linked with restoration of proper axial patterning in planaria by re-activation of appropriate WNT signaling [58] . Studies in hydra have similarly demonstrated that wound-responsive MAPK signaling is necessary for early specification of the head organizer, and thus functional regeneration.…”
Section: Early Features Of the Regenerative Response Are Deeply Consementioning
confidence: 99%